2014
DOI: 10.12816/0008212
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Response of the Cyclopoida Copepod Apocyclops Borneoensis Exposed to Nickel

Abstract: The use of biomarkers to evaluate the biological effects of pollutants in marine organisms represents a recent tool in biomontoring programs. The cyclopoida copepod Apocyclops borneoensis was exposed to different Ni treatments [0 (control), 10, 100, 1000 μg l-1 Ni] for 1, 2, 4, 7, 14 days. At each exposure time, acetylchlinesterase (AChE), superoxide dismutase (SOD), glutathione-S-transferase (GST), glutathione (GSH) were analyzed. Additionally, lipid peroxidation (LPO) level was measured after a 14-day exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…To protect against ROS, cells possess specific antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST), among others (Halliwell and Gutteridge, 2006;Mohammed, 2014). The level of lipid peroxidation, which leads to the formation of secondary products such as MDA, has been largely measured as indicator of injury caused by ROS in different marine organisms (Almeida et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To protect against ROS, cells possess specific antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST), among others (Halliwell and Gutteridge, 2006;Mohammed, 2014). The level of lipid peroxidation, which leads to the formation of secondary products such as MDA, has been largely measured as indicator of injury caused by ROS in different marine organisms (Almeida et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This study provides information on the ecotoxicological status of Chelon labrosus in the Milazzo Gulf, through the use of the esterase activities of AChE and BChE biomarkers, which have been validated as useful environmental diagnostic tools to recognize the presence of xenobiotic pollutants, such as insecticides in aquatic environments (Fossi et al 2002;Minutoli et al 2008Minutoli et al , 2013Fasulo et al 2010;Mohammed 2014;Parrino et al 2020). The neurotoxic effects of carbamates and organophosphates can be, in fact, evaluated by measuring the inhibition of the cholinesterase activity, even if many studies have also linked this inhibition to the toxic effects of heavy metal or hydrocarbon exposure (Payne et al 1996;Guilhermino et al 1998;Dethloff et al 1999;Sturm et al 1999;Parrino et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in another study Velisek et al (2014) showed that the activity of the antioxidant enzyme superoxide dismutase, was negatively affected in animals exposed to terbuthylazine, which can present profound impacts on production of MDA. On the other hand, another study (Mohammed, 2014) reported that a stimulatory effect of the activity of antioxidant enzymes occurred in a copepod species after being exposed to a metal (Ni). This lead to a reduction of MDA in those organisms.…”
Section: The Effect Of the Chemical Mixture On The Quality Of The Diamentioning
confidence: 99%